The variations of stride length and stride frequency in 100m sprint runs - Cunha, L.; Goncalves, I.; Dias, A.; Angelino, T. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The running velocity is determined by the stride length (SL) and stride frequency (SF), and 100 m sprint coaches usually use these parameters to assess racing proficiency. Many have been the trials to determinate which of these parameters are the most important in the final time of 100m-sprint race. From the literature we can conclude that the importance of these two parameters depend of the phase of the 100m run (at maximal velocity phase it is suggest that SF has a more decisive role than SL) and each sprinter have an optimal relationship between these two parameters, depending on numerousness variables (health, training preparation, morphological characteristics: height, leg length; physical, psychological, physiological and neural factors: speed, power, composition and structure of muscles, energy reserves, motivation, competitiveness; external factors: wind, location, weather, time scheduling, type and condition of the track surface). The variation of performance level of one athlete depend essentially on the variation of is stride length, stride frequency, or both? The purpose of this study was to analyze the behavior of the stride length and stride frequency in a 100 m run during a season and from year to year. We analyze 100 m races video recording (370) from 20 elite male sprinters (Desai Williams (10), Stefano Tilli (10), Robson da Silva (18), Olapade Adeniken (15), Linford Christie (36), Leroy Burrel (21), Jon Drummond (12), Frankie Fredericks (25), Maurice Greene (10), Donavan Baley (12), Dennis Mitchell (46), David Ezinwa (17), Carl Lewis (27), Calvin Smith (10), Bruny Surin, (30), Ben Johnson (15), Ato Bolton (12), Ray Stewart (26), Andre Cason (9), Dwain Chambers (9), since 1983 through `84,`87, `88, `91, `92, 93, `95, `96, `97, `99, 2000 major competition (Olympic Games, World Championship, European Championship) and European Circuit Athletics Meeting`s. We eliminate the runs were the athletes apparently don`t run in a full effort, (qualification heats, etc.) except the 9,79 Seuol 88` arm rise of Ben Johnson, the 9,96 and 10,00 Atlanta `96 Semi final from Frankie Fredericks and Donavan Baley, the 9,87 and 9,90 Athens `97 quarter finals from Ato Bolton and Maurice Greene. It wasn`t possible to establish by linear regression one common pattern variation of SL or SF for all sprinters, during a season or from year to year. There was in same cases an individual pattern of variation of SL and SF. Frequently the best`s performances were reach with the highest SL and SR, in spite of the strong correlation between the height or the leg length and the SL (it`s not the SR the only parameter to change). One important reason for this to happen is the wind; he has a major impact on the final times of 100m sprint runs. Sprinters with different drag area will experience different effect of the wind. The simple measurement of the wind was not enough because the wind is not constant, and only gives the total wind in 10 seconds measured at the wind-gauge site (is not possible to know if the wind is stronger in the first part of the race or even if the wind change is direction during the measurement). The velocity of the athlete (with is arms and legs velocities) is different in the first 2" of the race (acceleration phase) than in the rest of the race, and the velocity-time pattern influences the magnitude of the effect of wind on sprint times. The dependence of race times on wind velocity is real. The rate of improvement in race time gradually decreased with increasing wind velocity and so the disadvantage of a head wind was greater than the benefit of a tail wind of the same magnitude.